Microscale deformation mechanisms in paperboard during continuous tensile loading and 4D synchrotron X‐ray tomography. (13th April 2022) - Johansson, Sara; Engqvist, Jonas; Tryding, Johan; Hall, Stephen A.
Abstract: A better physical understanding of mesoscale and microscale mechanisms behind deformation and failure of paperboard material is important to optimize industrial packaging converting processes and decrease waste. In this study, these mechanisms were investigated using synchrotron X‐ray tomography during in situ continuous uniaxial tensile loading. High spatial and temporal data resolution enabled quantification of rapid changes in the material occurring before, during and after material failure. The evolution of 3D strain fields, fibre orientations and sample thickness showed that deformation and failure mechanisms differ significantly between samples tested in machine direction (MD), cross direction (CD) and 45° from the loading direction. In 45° and CD, gradual failure processes could be followed across several load steps. Immediately after failure, the in‐plane fracture region was significantly larger in both 45° and CD compared to MD. Both fracture characteristics and strain field distributions differed between the three material directions. Significant fibre reorientation was an active deformation mechanism in 45° already from the beginning of the loading, also present in CD after peak load but absent in MD. The MD‐dependent mechanisms interpreted and quantified at the scale of the fibre network in this study can help guide model development and likely have wider applicability to other paper‐based materials.